Mathematical modelling of cerebral ischaemia-reperfusion injury - Mokhtarudin, M (2016)
Restoring cerebral blood flow using reperfusion treatment is a common method in treating ischaemic stroke. Reperfusion treatment should be given within 4.5 hours from stroke onset. However, reperfusion beyond this time window poses the risk of reperfusion injuries such as intracranial haemorrhage and cerebral tissue swelling. The focus of this thesis is to study the effect of cerebral tissue swelling after reperfusion as it can occur in a few hours after the treatment. Cerebral tissue swelling may cause brain structure movement and cerebral microvessel compression; the latter may then lead to secondary ischaemia occurrence. In this thesis, two mathematical models are presented. The first model investigates the effect of ischaemia-reperfusion in the formation of cerebral tissue swelling. This model provides the understanding of suitable reperfusion conditions to reduce the effect of tissue swelling and also becomes the basis for the subsequent model. Meanwhile, the second model studies the role of a water-transporting protein, aquaporin-4 in ischaemia-reperfusion and its potential as part of treatments for cerebral tissue swelling. In addition, the ionic concentration may change during ischaemia which may be a factor contributing to cerebral tissue swelling. Thus, the effect of ionic concentration on the swelling formation is also investigated. Finally, validations of these models are achieved by developing patient-specific geometries from available ischaemic stroke patient MRI data and utilising finite element analysis. Comparison between the simulation results and the MRI data is done by quantifying the brain ventricles movement during cerebral tissue swelling.